Pattern recognition receptor signaling and innate immune responses to schistosome infection - Dibo, Nouhoum; Liu, Xianshu; Chang, Yunfeng; Huang, Shuaiqin; Wu, Xiang (Frontiers in Cellular and Infection Microbiology, 2022)
Schistosomiasis remains to be a significant public health problem in tropical and subtropical regions. Despite remarkable progress that has been made in the control of the disease over the past decades, its elimination remains a daunting challenge in many countries. This disease is an inflammatory response-driven, and the positive outcome after infection depends on the regulation of immune responses that efficiently clear worms and allow protective immunity to develop. The innate immune responses play a critical role in host defense against schistosome infection and pathogenesis. Initial pro-inflammatory responses are essential for clearing invading parasites by promoting appropriate cell-mediated and humoral immunity. However, elevated and prolonged inflammatory responses against the eggs trapped in the host tissues contribute to disease progression. A better understanding of the molecular mechanisms of innate immune responses is important for developing effective therapies and vaccines. Here, we update the recent advances in the definitive host innate immune response to schistosome infection, especially highlighting the critical roles of pattern recognition receptors and cytokines. The considerations for further research are also provided.